Getting social in selection: How social networking website content is perceived and used in hiring - Hartwell, Christopher J.; Campion, Michael A. (International journal of selection and assessment, 2020)
The use of social networking websites (SNWs) during employee selection is gaining popularity in organizations. Using a foundation that integrates identity and situational strength theories, we develop a conceptual framework that differentiates SNW information from information gathered through traditional selection procedures, and distinguishes between SNW types. Research questions and hypotheses are tested using a survey of 291 hiring professionals. Results indicate that SNW content is considered useful and is regularly utilized during hiring. Some SNW content is viewed positively (e.g., information supporting qualifications), while other information leads to negative perceptions (e.g., discriminatory comments). Finally, results support a differentiation between personal and professional SNW, as the kind of information sought and the effectiveness of assessing various work‐related constructs differs between these SNW categories.